(untitled) (Research, Society and Development, 2023)
The biomineralization technique of crack remediation in construction mortar can be achieved through the incorporation of calcifying bacteria within the mortar matrix. However, the thermal and autogenous shrinkage associated with the hydration of cement can be detrimental to the survival of the bacterial spores. Encapsulation of the spores in a matrix such as superabsorbent hydrogels, specifically sodium alginate, can provide protection from such detrimental conditions while also serving as a water reservoir for the metabolic activity of the bacterial cells. This paper investigated the addition of sodium alginate capsules prepared through spherification in construction mortars, aiming to preserve and optimize rheological, physical and mechanical properties, and to release bacteria when cracks occur. Mortar formulations with capsules containing Lysinibacillus sphaericus were calculated in order to maintain the granulometric distribution of standard formulation, thus obtaining products with excellent rheological, physical and mechanical properties, and allowing the addition of up to 1% capsules. Multivariate analysis of variance was applied at each age, showing that formulations with capsules kept the same properties as the original formula. After cracking, it was possible to observe the action of the released bacteria, through the formation of crystalline structures at the cracks. The capsules were prepared through a simple and cheap process, and it was proved that not only they do not affect concrete properties, but also are effective in both protecting the bacteria during mixing and hardening and releasing it after cracking.